AB0761 Synthesis and evaluation of the novel folate receptor ligand [18f]fluoro-peg-folate for macrophage targeting in a rat model of arthritis. (23rd January 2014) - Gent, Y. Y.; Weijers, K.; Molthoff, C. F.; Windhorst, A. D.; Huisman, M. C.; Smith, D. E.; Kularatne, S. A.; Jansen, G.; Low, P. S.; Lammertsma, A. A.; van der Laken, C. J.
Abstract : Background: Detection of (subclinical) synovitis is relevant for both early diagnosis and monitoring of therapy of rheumatoid arthritis (RA). Previously, the potential of imaging of (sub)clinical arthritis was demonstrated by targeting the translocator protein in activated macrophages using (R) -[ 11 C]PK11195 and positron emission tomography (PET) 1 . Images, however, also showed significant peri-articular background activity. The folate receptor (FR)-β has been recognized as a potential alternative target for imaging of activated macrophages as the receptor features high (nanomolar) binding affinities for folates and folate-conjugated therapeutic compounds. Objectives: Synthesis of the novel PET tracer [ 18 F]fluoro-PEG-folate and its evaluation in both in vitro and ex vivo studies using a methylated BSA induced arthritis model. Methods: [ 18 F]fluoro-PEG-folate was synthesized in a two-step procedure. Relative binding affinities of non-radioactive fluoro-PEG-folate, folic acid and naturally circulating 5-methyltetrahydrofolate (5-Me-THF) to FR were determined using KB cells with high expression of FR. Both in vivo [ 18 F]fluoro-PEG-folate PET and ex vivo tissue distribution studies were performed in arthritic rats on standard (high folate) or folate-deficient chow and in normal rats. Results were compared with those of the macrophage tracer (R) -[ 11 C]PK11195. Results: [ 18 F]fluoro-PEG-folate was synthesized with a purity >97%, a yield of 300-1700 MBq and a specific activity between 40-70 GBq/µmol. Relative in vitro binding affinity for FR of F-PEG-folate was 1.8 fold lower than that of folic acid, but 3 fold higher than that of 5-Me-THF. [ 18 F]fluoro-PEG-folate PET images clearly visualized arthritic rat knees. Confirming the PET data, [ 18 F]fluoro-PEG-folate uptake (in %ID/gram tissue) as determined by tissue distribution studies in arthritic knees (0.34±0.08) was increased compared with both contralateral knees (0.24±0.08) and knees of normal rats (0.16±0.04, p<0.01). Ex vivo uptake in arthritic knees could be blocked (0.03±0.02) by an excess of glucosamine-folate, consistent with [ 18 F]fluoro-PEG-folate being specifically bound to FR. Ex vivo arthritic knee-to-bone and arthritic knee-to-blood ratios of [ 18 F]fluoro-PEG-folate (1.64±0.15 and 23.1±14.3, respectively) were increased compared with those of (R) -[ 11 C]PK11195 (1.14±0.18 and 10.0±1.9, respectively). Reduction of 5-Me-THF levels in rat plasma to those mimicking human levels with folate-deficient chow increased absolute [ 18 F]fluoro-PEG-folate uptake in arthritic joints, but without improving arthritic knee-to-bone ratios. Conclusions: The novel PET tracer [ 18 F]fluoro-PEG-folate, designed to target FR on activated macrophages, provided improved contrast in a rat model of arthritis compared with the clinically established macrophage tracer (R) -[ 11 C]PK11195. These results warrant further exploration of [ 18 F]fluoro-PEG-folate as a putative PET tracer for imaging (sub)clinical arthritis in RA patients. References: Gent et al. Arthritis & Rheumatism 2012, 64, 62-66 Disclosure of Interest: None Declared